A review on progress of thiazole derivatives as potential anti-inflammatory agents - Kereyagalahally H. Narasimhamurthy; Toreshettahally R. Swaroop; Kanchugarakoppal S. Rangappa (European Journal of Medicinal Chemistry Reports)
Inflammation is a body response against infection that activates other biological components that include various cytokines, chemokines and other biological compounds that trigger body response against pathological activities. The Arachidonic acid pathway is involved in the inflammation that is connected with lipoxygenase (LOX) and cyclooxygenase (COX) enzymes. The importance of the isoforms of LOX and COX in inflammation is well studied. At the cellular level, some of the thiazole derivatives showed potent anti-inflammatory activities especially to block LOX5 and COX2 in the inflammation. These factors include both acute and chronic inflammation in various tissues like the heart, kidney, pancreas, brain, intestine, lungs and other organs as well that lead to the damage of the organs or cells. Whether it's the infectious or non-infectious response it will further activate some of the downstream signaling pathways like lipoxygenase, cyclooxygenase, cytochrome 450, JAK-STAT, MAPK, JNK, TNF-α, Nfr2, and many more pathways that lead to activation of another chronic disease in the body. In this review, we will concentrate on thiazole molecules that serve as anti-inflammatory responses to both acute and chronic inflammation. Further, we discussed the evidence that correlates the possible connection with LOX and COX enzymes in the inflammatory pathways and their blocking ability especially through thiazole derivatives has been discussed in this present review. The current assessment is the best part of the present consequence of thiazole derivatives on anti-inflammatory studies, covering articles published from 1973 to 2023.